Implementation of the Use of Village Funds in Supporting Development in Jatimulyo Village, Tulungagung Regency - Anggie Novita Rahmadani; Muhammad Agus Muljanto (Jurnal Kebijakan Publik, 2025)
Village funds are one part of village finances that come from APBN transfers and are used by village governments to improve the welfare of village communities in accordance with the priorities for using village funds. The policy on the use of village funds has been stated in Permendes Permendes Nomor 7 Tahun 2023 Tentang Rincian Prioritas Penggunaan Dana Desa. Village funds must be allocated for the welfare of the village community, one of which is through the realization of development. The purpose of this study is to describe the extent to which the implementation of the use of village funds in supporting development in Jatimulyo Village, Kauman District, Tulungagung Regency. The research method used is descriptive qualitative research and the research focus uses the theory of public policy implementation according to Van Meter & Van Horn (1975) which includes 6 variables. Based on the research results, the Jatimulyo Village Government and other implementers have implemented infrastructure development and human development through village funds in 2023. There are 3 out of 6 indicators that have not fulfilled the implementation theory according to Van Meter & Van Horn (1975), including: 1.) indicators of policy targets, the development carried out is the construction of GORs, farm roads, waterways, posyandu, and the Village Fund BLT program. However, these development targets have not been maximally useful in terms of quality and quantity. 2.) resource indicators, the limited village fund budget makes the implementers have to maximize these financial resources in supporting good development. 3.) indicators of the characteristics of these implementers still have insufficient competence in planning village development priorities at that time.